The Buenos Aires Central Wholesale Market (BACWN): A Case of Multiple Power - Laura Viteri, Maria (The International Journal of Sociology of Agriculture and Food, 2009)
The Buenos Aires Central Wholesale Market is a place where a lot of social and political relationships with different degrees of power are developed. Since this market was opened in 1984, the participating actors have faced several internal and external transformations, such as the implementation of neo liberal policies, changes in the Market’s administrative rules and the introduction of new actors in the retail distribution chain. Therefore, this article shows how international economic processes and policies become embedded in local distribution systems, and focuses on the spatial and social variability, i.e. the multiplicity of local social actors and interests involved in the globalization process. The article aims at exploring the creation of the Buenos Aires Central Wholesale Market as a constructed process linked with different kinds of social and political interests and motivations. In this respect, we combined the theoretical framework of political economy and the actor-oriented approach along with different ethnographic tools. The first one helps us to analyse the macro-dynamics of the market, whereas the second one allows us to analyse how people experience global processes in this particular social space. By doing so, we studied the strategies that actors developed in order to confront changes. Since the opening of the Buenos Aires Wholesale Market, these changes have modified the degree of economic and social relevance of the Market, thus generating different degrees of power in the actors involved.